Alterações na cinemática angular da marcha de pacientes hemiparéticos após acidente vascular encefálico - Lipreri, Luana Zanardi (My University, 2022)
Objective: To evaluate changes in the angular kinematics of gait in hemiparetic patients after stroke, comparing the affected side with the healthy side and with normality. Methods: This work is an observational, analytical study, with a cross-sectional approach, in which 17 hemiparetic individuals after stroke participated. The sample was selected at the physiotherapy clinic of the Universidade de Caxias do Sul. Gait analysis was performed in the gait laboratory of the same institution, following the Laroche protocol. The variables evaluated were speed and cadence, maximum angles of flexion and extension of the hip and knee, of the healthy and affected limbs. Descriptive statistics were used and for comparisons between limbs and normality, the paired t test and t test for one sample were used. The significance level adopted was p=0.05. Results: The sample consisted of 17 adult participants of both sexes. When comparing healthy and affected limbs, significant changes were observed in knee flexion (p=0.001) and extension (p=0.05), without great variability between the limbs in the hip angulations. Comparing the affected limb with normality, there was a significant difference in the angles of knee flexion (p<0.000) and hip extension (p=0.004), indicating less angular variation of these joints during gait. Conclusion: Patients with hemiparesis show changes in angular kinematics of gait when comparing the affected limb with the healthy and normal limbs. Assessing these changes is very important for the rehabilitation process of patients. [resumo fornecido pelo autor]
Objetivo: Avaliar as alterações na cinemática angular da marcha de pacientes hemiparéticos após acidente vascular encefálica, comparando o lado afetado com o sadio e com a normalidade. Métodos: Este trabalho é um estudo observacional, analítico, com abordagem transversal, onde participaram 17 indivíduos hemiparéticos após Acidente Vascular Encefálico. A amostra foi selecionada na clínica de fisioterapia da Universidade de Caxias do Sul. A análise de marcha foi realizada no laboratório de marcha da mesma instituição, seguindo o protocolo de Laroche. As variáveis avaliadas foram a velocidade e cadência, ângulos máximos de flexão e extensão do quadril e joelho, do membro sadio e afetado. Foi utilizada estatística descritiva e para as comparações entre os membros e normalidade, os testes teste t pareado e t para uma amostra. O nível de significância adotado foi p=0,05. Resultados: A amostra foi composta de 17 participantes adultos, de ambos os sexos. Ao comparar membro sadio com afetado foram observados alterações significativas em flexão (p=0,001) e extensão (p=0,05) de joelho, sem grande variabilidade entre os membros nas angulações do quadril. Comparando o membro afetado com a normalidade houve diferença significativa nas angulações de flexão de joelho (p<0,000) e extensão (p=0,004) de quadril, indicando menor variação angular destas articulações durante a marcha. Conclusão: Os pacientes com hemiparesia apresentam alterações na cinemática angular da marcha quando comparado o membro afetado com o sadio e com a normalidade. Avaliar essas alterações é muito importante para o processo de reabilitação dos pacientes. [resumo fornecido pelo autor]
Keywords: Fisioterapia; Acidente vascular cerebral; Cinemática; Análise da marcha; Paresia